Microbiological analysis of minimally processed fruits and vegetables marketed in supermarkets in the city of Macapá - Amapá (Research, Society and Development, 2020)
This work aimed to evaluate the microbiological quality, identifying the presence of Salmonella sp. and quantifying the most likely number of thermotolerant coliforms at 45 ° C / g in minimally processed fruits and vegetables. Three minimally processed samples of cabbage, pineapple, watermelon and carrot were collected, totaling 42 samples, 21 of which were from fruits and 21 from vegetables and roots, chosen randomly from refrigerated gondolas from 07 supermarkets in the southern area of the city of Macapá and taken to the microbiology laboratory of the Institute of Scientific and Technological Research of the State of Amapá - IEPA. After evaluation, it was observed that out of the 21 fruit samples analyzed, 5 showed results for thermotolerant coliforms above what is allowed by the legislation, which establishes the maximum value of 5x10² NMP / g. Of the 9 vegetable samples, 6 showed values higher than those established by legislation, which is 10² NMP / g for vegetables, and of the 12 roots analyzed, 9 were above the ideal for coliforms, which is 10³ NMP / g for roots, tubers and the like. All samples showed absent results for Salmonella sp., Showing themselves within the standards established by the RDC. It was possible to conclude that the minimally processed cabbage, pineapple, watermelon and carrot samples showed a higher concentration of thermotolerant coliforms than the limits established by RDC No. 12, of January 2, 2001, of ANVISA, indicating contaminations that compromise the quality of these and endanger consumer health